Modified double base propellants containing RDX with zero burning rate temperature coefficient - Chao Zhang; Xue-Xue Zhang; Ha Xiang; Xiao-hong Zhang; Qi-Long Yan (Energetic Materials Frontiers, 2025)
Low temperature sensitivity coefficients are of great significance for improving the combustion stability of modified double-base propellants (MDBPs) under sensitive environmental conditions. In this work, different combined catalyst systems containing Pb-complex, magnesium oxide (MgO), carbon black (CB) and Cu-complex have been employed to tune the combustion behavior of MDBPs. The effects of these catalysts on the combustion properties of MDBP have been comprehensively investigated at the pressure range of 4–15 MPa and different initial temperatures (−40, 20 and 50 °C). The MDBPs with composite catalysts of Pb-complex, MgO, CB and Cu-complex (NRPbMgCBCu) has almost zero temperature sensitivity coefficient. The combined catalyst systems have catalytic effect on thermal decomposition and combustion of MDBPs, which is more likely to cause an intensive combustion especially at lower pressures. The burning rate temperature sensitivity and pressure exponent of NRPbMgCBCu have been largely reduced by adding this combined catalyst systems. The results show that the exothermic peak temperature of NRPbMgCBCu was decreased by 8.2 °C, and its heat release has been increased by 26.4 %, whereas the heat of combustion is 4.1 % higher than that of the blank MDBP. More importantly, the burning rates of MDB propellants with catalysts are notably increased by 86.9 %–169.8 % at 4 MPa. The combination of Pb-complex, MgO, CB and Cu-complex may have the best stabilization effect on the burn rate sensitivity to the initial temperature for MDBPs. The calculated pressure exponent of NRPbMgCBCu at 6–12 MPa was largely reduced to 0.03, whereas the corresponding temperature sensitivity coefficient was only 5.4E-4 %·°C−1.